The complete mitochondrial genome of the Antarctic marine triclad, Obrimoposthia Wandeli (Platyhelminthes, Tricladida, Maricola) - Hee-Min Yang; Su-Jung Ji; Gi-Sik Min (Mitochondrial DNA. Part B. Resources, 2019)
For the first time, we report the complete mitochondrial genome (mitogenome) sequence of the marine triclad species, Obrimoposthia wandeli. The complete mitogenome of O. wandeli was 15,185 bp in length, contains 12 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), and 2 ribosomal RNAs (rRNAs). Compared to previously reported gene orders from the order Tricladida, O. wandeli had unique gene order. We constructed a phylogenetic tree based on the mitogenomes belonging to Rhabdocoela, Polycladida, and Tricladida and confirmed that O. wandeli is located in the basal position in the Tricladida.